FAKTOR-FAKTOR YANG MEMENGARUHI TERJADINYA LUKA KAKI DIABETIK PADA PASIEN DIABETES MELLITUS TIPE 2 DI BALAI PENGOBATAN DAN SPESIALIS PERAWATAN LUKA, STOMA, DAN INKONTINENSIA "KITAMURA" PONTIANAK PADA TAHUN 2014 - ., Adam Astrada (ProNers, 2014)
Diabetes mellitus (DM) is the seventh of the most leading causes of death in the world, where 15% ofthis case are at risk of diabetic foot ulcer. There are many factors affecting its occurence, but the mainfactors are still not well explored. This study aims to identify correlations between diet pattern,medication, smoking behaviour, physical activity, follow-up, foot care, psychological aspect, socialinteraction, spiritual aspect, and race/ethnicity toward diabetic foot ulcer occurence in type 2 DMpatients. This is a quantitative study with cross-sectional approach. Sample involved in this study is 88respondents, taken through accidental sampling method in "KITAMURA" Specialist Clinic of Wound,Stoma, and Incontinence Care, Pontianak. Univariate, bivariate with chi-square test, and multivariatewith logistic regression are used for data analysis. Bivariate analysis indicates that there are significantcorrelations between smoking behaviour (p = 0,008), follow-up (p = 0,011), and ethnicity (p = 0,000)towards diabetic foot ulcer occurence. Further, multivariate analysis shows factors affecting diabeticfoot ulcer are social interaction (p = 0,018; OR = 7,807), foot care (p = 0,028; OR = 5,566), smokingbehaviour (p = 0,007; OR = 0,110), psychological aspect (p = 0,008; OR = 0,110), Malays (p = 0,001;OR = 0,029), and Javanese ethnicities (p = 0,001; OR = 0,021). This study shows that social interactionand foot care are the main factors causing diabetic foot ulcer after affected by smoking behaviour andethnicity.Keywords : diabetic ulcer, diabetes, factorsReferences : 54 (1986 "“ 2014)